Salinity induced anatomical changes in maize (Zea mays L. cv. Bari-7) (Dhaka University Journal of Biological Sciences, 2014)
DOI: http://dx.doi.org/10.3329/dujbs.v23i1.19832Dhaka Univ. J. Biol. Sci. 23(1): 85-91, 2014